Analysis of microRNAs Expression Profiles in Madin-Darby Bovine Kidney Cells Infected With Caprine Parainfluenza Virus Type 3 - Li, Jizong; Mao, Li; Li, Wenliang; Hao, Fei; Zhong, Chunyan; Zhu, Xing; Ji, Xinqin; Yang, Leilei; Zhang, Wenwen; Liu, Maojun; Jiang, Jieyuan (Frontiers in Cellular and Infection Microbiology, 2018)
Caprine parainfluenza virus type 3 (CPIV3) is a newly emerging pathogenic respiratory agent infecting both young and adult goats, and it was identified in eastern China in 2013. Cellular microRNAs (miRNAs) have been reported to be important modulators of the intricate virus-host interactions. In order to elucidate the role of miRNAs in madin-darby bovine kidney (MDBK) cells during CPIV3 infection. In this study, we performed high-throughput sequencing technology to analyze small RNA libraries in CPIV3-infected and mock-infected MDBK cells. The results showed that a total of 249 known and 152 novel candidate miRNAs were differentially expressed in MDBK cells after CPIV3 infection, and 22,981 and 22,572 target genes were predicted, respectively. In addition, RT-qPCR assay was used to further confirm the expression patterns of 13 of these differentially expressed miRNAs and their mRNA targets. Functional annotation analysis showed these up- and downregulated target genes were mainly involved in MAPK signaling pathway, Jak-STAT signaling pathway, Toll-like receptor signaling pathway, p53 signaling pathway, focal adhesion, NF-kappa B signaling pathway and apoptosis, et al. To our knowledge, this is the first report of the comparative expression of miRNAs in MDBK cells after CPIV3 infection. Our finding provides information concerning miRNAs expression profile in response to CPIV3 infection, and offers clues for identifying potential candidates for antiviral therapies against CPIV3.